Geotechnical review for gypseous soils : properties and stabilization - Al-Yasir, Abdullah Talib; Al-Taie, Abbas Jawad (Penerbit Universiti Kebangsaan Malaysia, 2022)
In many arid and semi-arid regions, collapsible soils are well-known to be problematic in nature and negatively affect the performance of engineering structures. Gypseous soil considers one of the well-known types of collapsible soil. It represents a real challenge to engineers due to different problems encountered by engineering projects implemented in this soil. The mineralogy, composition, and fabric of gypseous soil affect its ability to deform when subjected to wetting (due to changing the whole structure soil particles). Numerous studies considered the problems of gypseous soils and their treatment with different additives and using different methods. In this paper, the properties of gypsum (physical appearances, hardness, density, chemical structure), gypsum effect on soil properties (specific gravity, compaction properties, shear strength), main geotechnical properties of gypseous soils, their problems, and different important additives (traditional and non-traditional) and methods used in gypseous soils problems mitigation have been discussed. Gypsum is one of unpredictable materials that have different forms, low hardness, and low density. Gypsum is the main occurring source of sulphate in soils, it affects their geotechnical properties to different degrees depending on its content, the presence of the other salts (than gypsum), soil gradation and type, and organic matters. There is a critical gypsum content beyond which gypsum negatively affects the shear strength of soils, this content is (10-20)%. Finally, although there are many additives used in the treatment of gypsum soil, the use of some additives should be done with caution to avoid destructive results, especially with clay gypseous soil.